Seasonal variations in biomass, height, photosynthetic efficiency, and carbon and nitrogen contents of Suaeda japonica in Incheon salt marshes (Korea) - Hwang, Jeong Hwa; Park, Ji-Sook; Han, Young-Seok; Yarish, Charles; Kim, Jang K. (Frontiers in Plant Science, 2025)
Salt marshes are known as major blue carbon ecosystems for their higher carbon sequestration capacity and productivity compared to terrestrial ecosystems. However, in Korea, salt marshes have been continuously decreasing since the 1980s. This study aims to identify seasonal changes in salt marsh plants and evaluate the carbon and nitrogen sequestration in these ecosystems. This study observed seasonal changes in the biomass, cover, height, photosynthetic efficiency, carbon and nitrogen content of Suaeda japonica in two salt marsh ecosystems in Incheon, Korea, Yeongjong (YJ) and Sorae (SR). In spring, plant density at SR. was significantly higher than at YJ. This higher density at SR inhibited growth and survival during summer and autumn. In addition, photosynthetic efficiency at SR decreased significantly in summer compared to spring. The different habitat densities between the two sites resulted in morphological variations. The plants at YJ, with lower density, grew wider with more branches and showed higher dry weight in comparison to those at SR. Carbon sequestration by S. japonica per unit area was 113.70 g/m2 at YJ, which was twice as high as at SR. The plant density and biomass of S. japonica were affected by differences in seawater inflow at each site. The tissue carbon content was highest in the roots, suggesting that carbon absorbed by the leaves is effectively stored in sediment. This study provides insights into the regional and seasonal changes of S. japonica, highlighting its significance as a blue carbon resource. The results can contribute to the evaluation and restoration of salt marshes to enhance their carbon sequestration potential.